(untitled) (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. This article analyses the perceptual aspect of professional and communicative activity. The essence and peculiarities of communicative activity as a process of subject-subject cooperation were found. The psychological basis of the perceptual side of communicative activity was established, which forms communicative abilities reflected in the ability to know and objectively interpret the external manifestations of the perceived person. The system of perceptual skills as an important component and condition for successful interaction of people in the process of joint activity is presented and described. The psychological mechanisms of effective perception, understanding, evaluation and creation of an adequate image of a partner by cooperation and their characteristics were defined.